From agricultural to economic growth: Targeting investments across Africa - Tigabu Degu Getahun; Heike Baumüller; Yalemzewd Nigussie (University of Bonn, Center for Development Research (ZEF), 2018)
This paper examines whether investment in the agriculture and food sectors in Africa significantly increases overall economic growth and, hence, reduces food and nutrition insecurity. To this end, the study examines the causal link between agricultural growth, food production, quality of governance, and overall economic growth using panel data compiled from 44 African countries for a 53-year period from 1961 to 2014. The estimation result from the fully modified least squares, the panel cointegration, and Granger causality tests suggest that agricultural growth, government commitment, and quality of governance Granger causes overall economic growth. The study also identifies the 10 African countries where investment in the agriculture and food sectors is expected to yield the highest returns and the 10 African countries having the lowest returns in terms of reducing food insecurity and poverty. The result indicates that Botswana, Burkina Faso, Ethiopia, Kenya, Malawi, Mali, Mozambique, Rwanda, Seychelles, and Sierra Leone are the top 10 African countries where such an investment is expected to yield the highest returns. Cameroon, Congo, Egypt, Equatorial Guinea, Eritrea, Gabon, Gambia, Libya, Mauritania, and Somalia are the bottom 10 countries where such investment is expected to yield the lowest return.
Keywords: 330; Granger causality; Agricultural growth; Economic growth; Investment return; Africa